Ensino de artes visuais na modalidade a distância: contribuições dos objetos de aprendizagem de artes visuais no processo de ensino/aprendizagem - Jose Maximiano Arruda Ximenes de Lima (2013)
This thesis discusses the relations between Visual Arts Learning Objects (OAAV), cognition and the teaching of Visual Arts through distance learning. Those subjects were dealt with on the basis of theories from Efland (2004), Barbosa (2008), Pimentel (1999) and Silva (2002). The aim of this study is to investigate the contributions of OAAVs to distance learning courses of Visual Arts, seeking to formulate a specific proposal for the preparation of OAAVs. Thereunto, we used the qualitative methodology with case study, interviews, questionnaires, observations and tests. The case study was carried out in a distance learning course of Visual Arts in Ceará, Brazil. In that course, we observed two classes; in each one we observed two theoretical disciplines and two practical subjects, adding up to eight case studies. Those data were analyzed by using the following codifications: a) teacher/student interaction; b) ability to draw and paint before and after taking the discipline; c) usability and interactivity of the posted object; d) understanding and development in the discipline after using the OAAV; e) skill development through the OAAV; f) ability to analyze an image formally. Therefore, we presente a proposal for the establishment of OAAVs, and foster their creation, requirements, characteristics, and classification. Finally, we expose the contributions of OAAVs in the teaching/learning process in distance learning courses of Visual Arts.